The characteristics of several varieties and the effect of cropping management design on the level of pest damage and seed yield of soybeans in rainfed lowland rice fields - Fattah, Abdul; Hannan, Muhammad Fitrah Irawan; Yasin, M.; Harnowo, Didik; Nugraha, Yudhistira; Wulanningtyas, Heppy Suci; Najamuddin, Erwin; Saenong, Sudjak; Rahman, Ayyub Ar; Winanda, Elisa; Hasanuddin, Rahmi; Rohimatun; et al. (Frontiers in Sustainable Food Systems, 2024)
Design of crop method and type of variety is one of the most important factors in increasing soybean productivity and the level of pest attack and predator populations. This study aims to determine the most effective planting method and variety types in an effort to increase soybean productivity in rainfed lowland areas in South Sulawesi, Indonesia. The design used in this study was the Split Plot Design, the varieties (PU) used were: 1) Detap-1, 2) Devon-1, and 3) Derap-1, while the subplot (AP) was a planting method and three replicates. time.Varieties (PU) used: 1) Detap-1, 2)Devon-1, and 3) Derap-1, while the subplot (AP) is a planting method: 1) Farmers transplanting method (transplanting row: 20 cm x 20 cm), 2) Method of transplanting double rows, and 3)Method of transplanting three rows. The results showed that the highest number of branchesper plant was in the Legowo-3 planting method with the Detap-1 variety. The lowest level of leaf damage due to Spodoptera litura attack was in the Legowo double rows planting method on theDevon-1 variety (11.07%) and the highest on the jajar horn planting method (farmer's method) onthe Derap-1 variety (16.47%).The level of pod damage due to Etiella zinckenella attack was the lowest on Legowo-3 on the Derap-1 variety (9.47%) and the highest on the double rows planting method on the Detap-1 variety (14.26%). The level of pod damage due to attack by pod-sucking Pest Riptortus linearis was the lowest on Legowo-3 on the (Derap-1) variety (8.02% and the highest on the pod-sucking pest Riptortus linearis on the Devon-1 variety (13.43%).The length ofthe trichomes on soybean leaves was the highest on the Devon-1 variety (30.93%) and the loweston Derap-1 (24.81).The highest number of trichomes on soybean leaves was on the Derap-1variety (57.67) and the lowest on the Devon-1 variety (32.20).The highest length of trichomeson soybean pods on Detap-1 (29.11) and lowest on Devon-1 (26.52).While the highest numberof trichomes in soybean pods was on Devon-1 (222.47) and lowest on Derap-1 (148.40).The highest seed yield was on Legowo-3 with variety Derap-1 and Devon-1 (2.02-2.08 t ha -1 ).